Schistosomiasis screening in non-endemic countries from a cost perspective: Knowledge gaps and research priorities. The case of African long-term residents in a Metropolitan Area, Spain. - Sílvia Roure; Francesc López; Irene Oliva; Olga Pérez-Quílez; Oriol March; Anna Chamorro; Elena Abad; Israel López Muñoz; Amaia Castillo; Laura Soldevila; Lluís Valerio; Manolo Lozano; et al. (Public Library of Science (PLoS), 2023)
Background Imported schistosomiasis is an emerging issue in European countries as a result of growing global migration from schistosomiasis-endemic countries, mainly in sub-Saharan Africa. Undetected infection may lead to serious long-term complications with an associated high cost for public healthcare systems especially among long-term migrants. Objective To evaluate from a health economics perspective the introduction of schistosomiasis screening programs in non-endemic countries with high prevalence of long-term migrants. Methodology We calculated the costs associated with three approaches-presumptive treatment, test-and-treat and watchful waiting-under different scenarios of prevalence, treatment efficacy and the cost of care resulting from long-term morbidity. Costs were estimated for our study area, in which there are reported to reside 74,000 individuals who have been exposed to the infection. Additionally, we methodically reviewed the potential factors that could affect the cost/benefit ratio of a schistosomiasis screening program and need therefore to be ascertained. Results Assuming a 24% prevalence of schistosomiasis in the exposed population and 100% treatment efficacy, the estimated associated cost per infected person of a watchful waiting strategy would be €2,424, that of a presumptive treatment strategy would be €970 and that of a test-and-treat strategy would be €360. The difference in averted costs between test-and-treat and watchful waiting strategies ranges from nearly €60 million in scenarios of high prevalence and treatment efficacy, to a neutral costs ratio when these parameters are halved. However, there are important gaps in our understanding of issues such as the efficacy of treatment in infected long-term residents, the natural history of schistosomiasis in long-term migrants and the feasibility of screening programs. Conclusion Our results support the roll-out of a schistosomiasis screening program based on a test-and-treat strategy from a health economics perspective under the most likely projected scenarios, but important knowledge gaps should be addressed for a more accurate estimations among long-term migrants.